2019
DOI: 10.1021/acs.chemmater.9b00893
|View full text |Cite
|
Sign up to set email alerts
|

MnO2-Disguised Upconversion Hybrid Nanocomposite: An Ideal Architecture for Tumor Microenvironment-Triggered UCL/MR Bioimaging and Enhanced Chemodynamic Therapy

Abstract: Upconversion nanoparticles (UCNPs) and MnO 2 hybrid theranostic nanoplatform (UCMn) is highly desired; however, the rational design of such UCMn hybrid nanomaterials is still a great challenge. Herein, a simple and versatile strategy for the in situ growth of MnO 2 on the surfaces of UCNPs was reported using a sacrificial template method to construct an ideal MnO 2 -disguised and tumor microenvironment−triggered architecture. Such sophisticated architecture not only achieves activatable magnetic resonance imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 45 publications
2
88
0
Order By: Relevance
“…Moreover, compared with Mn 2+ ‐mediated CDT, MnO 2 is able to generate more •OH and show higher cytotoxicity demonstrated with both in vitro and in vivo studies because of GSH depletion by MnO 2 . After that, more researches further proved the ability of MnO 2 for CDT 21,46d. Furthermore, Cai group also confirmed that MnO NPs have the capacity of producing free radical for CDT …”
Section: Therapeutic Applicationsmentioning
confidence: 93%
See 3 more Smart Citations
“…Moreover, compared with Mn 2+ ‐mediated CDT, MnO 2 is able to generate more •OH and show higher cytotoxicity demonstrated with both in vitro and in vivo studies because of GSH depletion by MnO 2 . After that, more researches further proved the ability of MnO 2 for CDT 21,46d. Furthermore, Cai group also confirmed that MnO NPs have the capacity of producing free radical for CDT …”
Section: Therapeutic Applicationsmentioning
confidence: 93%
“…Furthermore, it is worth noting that different valences of manganese ions exhibit discrepant toxicity. For example, compared with Mn 2+ ions, it has been proved that MnO 2 (Mn 4+ ions) at the same manganese content showed higher cancer cells killing due to GSH depletion by MnO 2 6c,21. In short, for biomedical applications, manganese valence states among oxides are very important.…”
Section: The Chemical Properties Surface Engineering and Toxicity Omentioning
confidence: 99%
See 2 more Smart Citations
“…Aiming at solving this restriction, several nanomaterials with GSHconsumption ability have been developed and used for tumor theranostics. [78][79][80][81] Li et al prepared copper-amino acid mercaptide NPs (Cu-Cys NPs) with GSH-triggered and H 2 O 2 -enhanced CDT abilities for resisting breast tumors ( Fig. 11A and B).…”
Section: Enhanced Chemodynamic Theranostic By Regulating the Tmementioning
confidence: 99%